Relationship between dormancy and its release and external factors in tubers of water yam (Dioscorea alata L.) - Park, B.J.; Onjo, M.; Tominaga, S.; Shiwachi, H.; Hayashi, M. (2003)
To analyze the mechanism of dormancy in tubers of water yam (Dioscorea alata L.), we studied the relationship between external factors and dormancy and its release in tubers. Several strains of water yam that have been introduced into Japan from Southeast Asia and Oceania were grown in Kagoshima, Japan. Dormancy period ranging from 2 to 4 months in length (from harvest to sprouting), has been observed in 48 strains that were tested at 25 ℃. It was found that the duration of the dormancy period differed among the strains. The moisture content of the tubers decreased with storage time. Although the mean of the ratio of decreasing fresh weight found in 48 strains that were stored for 90 days was 20.5%, each strain differed in the tuber moisture content after the 90-day storage period. However, comparison of the group of strains with long dormancy with the group of strains with short dormancy showed that the ratio of decreasing fresh weight of the tubers did not differ between two groups. Thus the ratio did not appear to be related to the dormancy of water yam tubers. The duration of the dormancy period of 4 early maturing, 37 medium maturing, and 7 late maturing strains was determined and found to be 65, 66, and 61 days, respectively.